Irisin as a Novel Biomarker of Subclinical Atherosclerosis, Cardiovascular Risk and Severe Disease in Axial Spondyloarthritis - Remuzgo-Martínez, Sara; Rueda-Gotor, Javier; Pulito-Cueto, Verónica; López-Mejías, Raquel; Corrales, Alfonso; Lera-Gómez, Leticia; Pérez-Fernández, Raquel; Portilla, Virginia; González-Mazón, Íñigo; Blanco, Ricardo; Expósito, Rosa; Mata, Cristina; et al. (Frontiers in Immunology, 2022)
Introduction: Patients with axial spondyloarthritis (axSpA) have a high disease burden mainly due to the rheumatic disease itself, and also exhibit accelerated atherosclerosis, that leads to a higher incidence of cardiovascular (CV) disease. Accordingly, the identification of biomarkers of CV risk and inflammation in axSpA patients is clinically relevant. In this sense, given the beneficial functions exerted by the adipomyokine irisin in processes related to CV disease and inflammation, our aim was to assess, for the first time, the role of irisin as a genetic and serological biomarker of subclinical atherosclerosis, CV risk and disease severity in axSpA patients. Methods: A large cohort of 725 Spanish patients with axSpA was included. Subclinical atherosclerosis (presence of plaques and abnormal carotid intima-media thickness values) was evaluated by carotid ultrasound. Four irisin polymorphisms (rs16835198 G/T, rs3480 A/G, rs726344 G/A, and rs1570569 G/T) were genotyped by TaqMan probes. Additionally, serum irisin levels were determined by ELISA. Results: Low irisin levels were linked to the presence of plaques (p=0.002) and atherogenic index values ≥4 (p=0.01). Serum irisin were positively correlated with C-peptide levels (p<0.001) and negatively correlated with visual analogue scale and Bath Ankylosing Spondylitis Metrology Index (p<0.05 in all the cases). Moreover, lower irisin levels were observed in patients with sacroiliitis and in those with a negative HLA-B27 status (p<0.001 and p=0.006, respectively), as well as in those treated with non-steroidal anti-inflammatory drugs and conventional disease-modifying antirheumatic drugs (p<0.001 and p=0.002, respectively). Interestingly, the TT genotype and the T allele of rs16835198 were less frequent in axSpA patients with ASDAS >2.1 (Odds Ratio (OR): 0.48 [0.28-0.83] and OR: 0.73 [0.57-0.92], respectively, p=0.01 in both cases). Additionally, the frequency of rs1570569 T allele was higher in these patients (OR: 1.46 [1.08-1.97], p=0.01). Furthermore, the GGGT haplotype was more frequent in patients with ASDAS values >2.1 (OR: 1.73 [1.13-2.66], p=0.01). Conclusions: Our results indicate that low serum irisin levels could be indicators of the presence of subclinical atherosclerosis, high CV risk and more severe disease in axSpA patients. In addition, irisin may also constitute a genetic biomarker of disease activity in axSpA.